2020
DOI: 10.1371/journal.pntd.0007965
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and analytical validation of a new antigenic rapid diagnostic test for Ebola virus disease detection

Abstract: Hemorrhagic fever outbreaks are difficult to diagnose and control in part because of a lack of low-cost and easily accessible diagnostic structures in countries where etiologic agents are present. Furthermore, initial clinical symptoms are common and shared with other endemic diseases such as malaria or typhoid fever. Current molecular diagnostic methods such as polymerase chain reaction require trained personnel and laboratory infrastructure, hindering diagnostics at the point of need, particularly in outbrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Several other EBOV rapid diagnostic tests were generated and some of them were approved during the outbreak [ 28 ]. A recent study reported generation of an sGP and GP detection kit based on immunochromatography coupled with silver amplification technology [ 11 ]. The limit of detection for this assay was 2.21 × 10 4 genome copies/mL in plasma samples from an infected NHP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other EBOV rapid diagnostic tests were generated and some of them were approved during the outbreak [ 28 ]. A recent study reported generation of an sGP and GP detection kit based on immunochromatography coupled with silver amplification technology [ 11 ]. The limit of detection for this assay was 2.21 × 10 4 genome copies/mL in plasma samples from an infected NHP.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 20–30% are left for the edited 8A full-length GP which is expressed on the virion surface, and the edited 9A small sGP (ssGP) [ 9 , 10 ]. Even though sGP is transcribed and expressed at a higher level compared to GP and is detected in the blood of EBOV-infected animals and humans, only few diagnostic tests targeting sGP exist [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Facile, facilitated tests are required to detect and manage the Ebola endemics earlier tests which are capable of detecting the virus in blood at highly little quantities. The WHO announced rapid, sensitive, safe, and simple EBOV diagnostic assays in November 2014 [ [65] , [66] , [67] ]. Wen et al.…”
Section: Application Of Carbon Nanomaterials For Viral Diagnosismentioning
confidence: 99%
“…Ebola Viral Disease (EVD) is a severe and overwhelmingly fatal disease [30]; death rate is approximately 80% among those infected. It is caused by the EBOV, a member of the filovirus family and occurs in humans and other primates [31]. An EBOV is a single-stranded, non-segmented, and negativesense RNA virus.…”
Section: Ebola Virus Diseasementioning
confidence: 99%
“…EBOVs are thought to be zoonotic; however, their original reservoir has yet to be confirmed. African fruit bats are regarded as the most likely natural reservoir for EBOVs [31,33]. Initial human infection with Ebola virus occurs through contact with an infected animal, such as a fruit bat or other non-human primate.…”
Section: Ebola Virus Diseasementioning
confidence: 99%